1998
DOI: 10.1042/bj3310041
|View full text |Cite
|
Sign up to set email alerts
|

The C-terminus of factor H: monoclonal antibodies inhibit heparin binding and identify epitopes common to factor H and factor H-related proteins

Abstract: We have generated monoclonal antibodies (mAbs) specific for the C-terminus of factor H that can be used as inhibitory antibodies for heparin binding and for the specific detection of factor H and factor H-related proteins (FHRs) in plasma and triacylglycerol-rich lipoproteins. Four distinct mAbs were established: IXF9 (IgG1), VD3 (IgG2a), VIG8 (IgG1) and IIC5 (IgG1). Each reacts specifically with FHR-1 and factor H (and also with FHR-2 in the case of VIG8), but none binds to the related FHR-3 and FHR-4 protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 11 publications
5
55
0
1
Order By: Relevance
“…Since the non-activating surfaces usually contain negatively charged surface structures (sialic acids and glycosaminoglycans), interactions between fH and polyanions have been intensively characterized. FH has been found to contain two or three binding sites for heparin and/or sialic acid on SCR7, SCR20, and possibly SCR12-14 (23)(24)(25)(26)(27)(28). It has been suggested that these heparin-binding sites have a role in the ability of AP to discriminate between activators and nonactivators; however, the physiological role of these sites is not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the non-activating surfaces usually contain negatively charged surface structures (sialic acids and glycosaminoglycans), interactions between fH and polyanions have been intensively characterized. FH has been found to contain two or three binding sites for heparin and/or sialic acid on SCR7, SCR20, and possibly SCR12-14 (23)(24)(25)(26)(27)(28). It has been suggested that these heparin-binding sites have a role in the ability of AP to discriminate between activators and nonactivators; however, the physiological role of these sites is not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Cloning, expression in the baculovirus system, and purification of most of the used recombinant fragments of fH have been described earlier (27,36,50). Also the additional fragments representing SCR8-11, SCR15-18 and SCR15-20 were generated using the pBSV-8His expression vector (50).…”
Section: Recombinant Fragments Of Fhmentioning
confidence: 99%
“…The structural similarity and the sequence identity of individual protein domains suggest overlapping function(s) of FHR proteins and activities shared with the complement and immune regulator Factor H. 7 FHRs and Factor H bind the same ligands, as demonstrated for C3b (FHR-1, FHR-3, FHR-4 and FHR-5), 8 -10 heparin (FHR-1 and FHR-3, FHR-5), 8,9,11,12 Creactive protein (FHR-3 and FHR-4) 13 and some subtypes of the streptococcal M protein (FHR-3). 14 FHR-1, FHR-2 and FHR-4 as well as Factor H are present in plasma lipoproteins and FHR-5 has been found in kidney glomerular complement deposits.…”
Section: Introductionmentioning
confidence: 99%
“…Human C5 was purchased from Calbiochem (La Jolla, CA). Recombinant proteins FHL-1 (representing the N-terminal seven SCRs of factor H plus four unique additional amino acids), SCRs 8 -20 and SCR 15-20 of factor H, factor H-related proteins FHR-3 and FHR-4, and a construct SCR 1-4 of FHR-3 were expressed with the baculovirus expression system as described previously (31)(32)(33)(34). The recombinant proteins were purified by Ni 2ϩ -chelate chromatography as described (35).…”
Section: Expression and Purification Of Complement Components-plasmamentioning
confidence: 99%